EXPLORING THE LIVED EXPERIENCES OF ESL TEACHERS IN THE TEACHING OF ENGLISH SUBJECTS - Castro, Jocelyn Sabas (Sanata Dharma University, Yogyakarta, 2023)
Teaching English has been a major issue in countries where English is not the first language, making it difficult for L2 learners to learn a second language because they cannot use English in real-life situations. However, pronunciation is a significant element of English language fluency. It is considered to be essential for successful oral communication. This paper documented the lived experiences of five ESL teachers in teaching English classes at Eastern Samar State University, Guiuan. This study employed a transcendental phenomenology research design. The five selected teachers teaching English subjects were asked to share their experiences through an in-depth interview in teaching English subjects and their observed students’ English language challenges. The data gathered generated five themes, which included sensitivity among students on error correction; divergent attitudes of the students towards pronunciation instruction; pronunciation errors of students in both segmental and suprasegmentals; teacher’s ways of dealing with the level of extent of students’ fossilization period; and challenges in teaching the English language. The result implies that students’ lack of exposure to language learning opportunities contributes to the emerging problem in the fluency of the language. Therefore, challenges to ESL teachers in dealing with students’ difficulties in learning the English language.